Modulation on Glutamic Pathway of Frontal-Striatum-Thalamus by rs11146020 and rs3813296 Gene Polymorphism in First-Episode Negative Schizophrenia - Cai, Suping; Lv, Yahui; Huang, Kexin; Zhang, Wei; Wang, Qiang; Huang, Liyu; Wang, Jijun (Frontiers in Neuroscience, 2020)
Objectives: The frontal-striatum-thalamus pathway is important in the glutamic neural circuit. The hypofunction of GRIN1 and GRIA2 subunits from glutamic receptors has been hypothesized as the primary process in the etiology of schizophrenia. Identified gene polymorphism involved in the pathogenesis of schizophrenia may uncover relevant mechanism pathways. Methods: We selected two loci of rs11146020 and rs3813296 distributed in GRIN1 and GRIA2 genes and tested their main and interaction effects on causality connections and structural characteristics in the frontal-striatum-thalamus pathway in 55 Han Chinese first-episode negative schizophrenia patients. Results: We found that: 1) rs11146020 has a significant main effect on the causality connections between the bilateral dorsolateral prefrontal cortex, and rs3813296 mainly influences those of the descending pathway from the prefrontal cortex to the striatum; 2) interaction effect of rs11146020 and rs3813296 on causality connections are located in the ascending pathway from the pallidum to the dorsolateral prefrontal cortex; and 3) the two loci have effects on the volumes of several regions of this pathway. Conclusions: Our results suggested there is modulation on glutamic frontal-striatum-thalamus pathway by rs11146020 and rs3813296 gene polymorphism. Patients with different genotypes have different neuroimaging characteristics, which indirectly reminded clinicians those patients should receive different clinical interventions.